Unified European support framework to sustain the HIV cascade of care for people living with HIV including in displaced populations of war-struck Ukraine. Issue 6 (June 2022) - Vasylyev, Marta; Skrzat-Klapaczyńska, Agata; Bernardino, Jose I; Săndulescu, Oana; Gilles, Christine; Libois, Agnès; Curran, Adrian; Spinner, Christoph D; Rowley, Dominic; Bickel, Markus; Aichelburg, Maximilian C; Nozza, Silvia; et al.
Summary: Ukraine is one of the countries in Europe most affected by HIV. The escalation of open war on the European continent has affected HIV care in Ukraine in an unprecedented way. Treating physicians in Europe have little experience on how to handle HIV-specific care under these circumstances. A framework is urgently needed that both defines and sets out strategies to handle the specific challenges for emergency support for people living with HIV, both those staying in Ukraine and those becoming displaced. The optimal allocation of the few available medical resources, primarily antiretroviral therapy, is necessary to best prevent individual morbidity and achieve population transmission control. Professional HIV networks play a central role to create, optimise, and execute support strategies. Through a rapid literature review we identified the key strategies needed to create a support framework, adapted to Ukraine's HIV epidemiology. We produce a unified support framework aiming to reduce the inevitable impact on Ukraine's HIV care cascade now, and when rebuilding it after the war.